Trace Metal Contamination During Grinding of Plant Samples. Issue 1 (2nd January 2019) - Bich, Luong Bui; My, Hanh Phung Thi; Dinh, Rinh Pham; Minh, Trang Pham; Trong, Thang Do; Harper, Stephen; Wuhrer, Richard; Huang, Qingtao; George, Laurel; Holford, Paul; Zhao, Chen Chen; Mitchell, Christopher; et al.
ABSTRACT: Inductively coupled plasma-mass spectroscopic (ICP-MS) analysis of leaves from 22 cabbage crops in the Sa Pả and Bắc Hà districts of Láo Cai Province, North-Western Việt Nam, revealed unexpectedly high concentrations of chromium (Cr) and nickel (Ni). The concentrations were strongly linearly related (r 2  = 0.94), indicating sample contamination during grinding through a stainless-steel hammer mill. We tested this hypothesis in two ways. First, brown rice ground through the same mill was contaminated not only by Cr and Ni, but also cobalt (Co), iron (Fe) and molybdenum (Mo). Second, scanning electron microscopy/energy dispersive analysis of x-rays (SEM/EDS) of the ground samples revealed small fragments with co-located Fe, Cr and Ni, consistent with stainless steel wear fragments. Other grinders may perform differently and we suggest that quality assurance protocols for trace metal analysis of plants should include testing for grinder wear metals. Lastly, brown rice appears to be convenient for investigating contamination of plant tissues during grinding.